Cyber vulnerabilities in smart grid and safety measures for energy meters in advanced metering system and smart meter communications - Ayob A.; Salim Reza S.M.; Hussain A.; Saad M.H.M.; Amin N. (World Academy of Research in Science and Engineering, 2023)
A smart grid (SG) utilizes many electronic devices that can communicate within the system and remain internally connected through implementing advanced Information and Communication Technologies (ICT). This paper analyzes the complete structure of a smart grid system, implementation of technologies such as Supervisory Control and Data Acquisition (SCADA) and smart metering, as well as identifies the potential cyberthreats. As the connected devices have significant limitations in terms of resource and computational processing power, it calls for developing a lightweight safety measures for those devices which would require low processing power and can operate instantaneously without outside intervention. Based on such requirement, this paper has proposed a lightweight and easily implementable safety measure for Advanced Metering Infrastructure (AMI) using ChaCha20 encryption model. It also uses chaos based key generation as well as public key-based authentication techniques. Besides, to ensure security of the network communication, a solution has been proposed using Elliptic Curve Cryptography (ECC) in combination with Salsa20 stream cipher algorithm. Comprehensive mathematical simulations have been conducted for both methodologies to examine their effectiveness in the real world, and to analyze whether they are efficient in terms of time and processing power. It has been found out that Salsa20 is more energy-efficient encryption tool, which is also faster, making it the perfect choice for smart metering devices. 2019, World Academy of Research in Science and Engineering. All rights reserved.